Features of aesthetic education of teenagers using fine arts - Demjanchuk, Oleksandr (Professional Art Education, 2023)
The purpose of the article is to determine the features and mechanisms of modernization of pedagogical conditions of aesthetic education of adolescents by means of fine arts, to analyze modern innovative technologies used in this process. Methods and methodology. The methodological basis and an important principle of aesthetic education at the present stage is the idea of an integrated approach, which in the implementation of the system of aesthetic education has a double meaning: the system of aesthetic education should be built on the basis of artistic images that constantly interact with each other in the process of influencing the adolescent, that is, the need for close interaction of art on the basis of interdisciplinary connections is organized; aesthetic education as education by means of the visual arts and by means of reality should become an organic part of the process of aesthetic education. Theoretical methods are used in the article: comparison, systematization and generalization of scientific sources on the use of fine arts as a means of aesthetic education of adolescents. The scientific novelty of the article is to clarify the content of the concept of "aesthetic education", to propose organizational and pedagogical conditions that ensure the effectiveness of aesthetic education of adolescents in the process of teaching fine arts. Results. The positive role of subjective perception and experience of works of art, which allow to realize their objective aesthetic meaning, is recognized. The significance of thinking activity, the ability of adolescents to "co-action" and "empathy" through figurative and conceptual generalization is revealed. The relationship between the individual (specific sensory form, figurative generalization) and the general (sensory perception of the multifaceted essence of the depicted phenomenon) is analyzed. The content of the reproductive (fragmentary and plot sublevels); emotional-artistic; intuitive-artistic; and conscious-artistic levels of perception of works of fine art is substantiated. The results of the study can be used in the pedagogical practice of primary schools, as well as for the development of teaching aids, didactic materials for pedagogical institutions of secondary and special education, higher education institutions.